The Limits to Growth — 50 Years Ago and Today - Thomas Döring; Birgit Aigner-Walder (Intereconomics)
Abstract The Limits to Growth was published 50 years ago. Ordered by the Club of Rome, the study was a milestone in the analysis of the economic, demographic, technical and ecological effects of the existing economic system. In industrialised Western countries in particular, the critical examination of the development model of continuous economic growth led to a broad discussion about the far-reaching implications of a global economy focusing on growth, on a planet with finite natural resources.